IBM KELOMPOK USAHA HASIL LAUT PULAU LAE-LAE MAKASSAR - Rahmawati, Rahmawati (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2017)
Micro, small and medium business group is a labor-intensive, the use of a relatively small venture capital and technology tend to be simple. This business group has the potential to improve living standards. On the island of Lae-Lae District of Ujung Pandang Makassar City there are groups of small and medium enterprises (SMEs) that the Sinar Lae-Lae and the Anggur group. SME group is developing marine products such as fish, squid and seaweed. This business group has a lot of innovation in producing seafood products such as meatballs, shredded fish, sweets and crackers seaweed. The results of the discussion and identification of problems in the production of a group of SMEs found that the amount of production is limited because of production activities take place only at night when the electricity supply is available. Variations seaweed crackers produced limited and the packaging of the product be done without tools vacuum sealer. In addition, the packaging of sweets seaweed less attractive, is not hygienic and does not include the date of production. Targets were achieved in both groups of SMEs are to increase production through the installation of solar panels so that the production process can be done not only at night but also during the day. In addition, create a variant form of seaweed crackers crackers using molds, packaging more attractive by means of vacuum sealer, hygiene and labeling of products produced.